Hadapi Tantangan Global, Lembaga Pendidikan Hindu Harus Jadi Gurukula Modern - Ni Kadek Surpi (Jurnal Penjaminan Mutu, 2017)
Education is very important factor in building civilization. A civilization or a country will advance rapidly when its education system give such a great contributions to the development of Human Resources. The advancement of a nation is determined by the extent of the educational institution which has succeeded in building its human being into a superior human being, in order to be a dignified world citizen. Hindu civilization greatly emphasizes the importance of education. In the history of Sanatana Dharma, education gets an enormous portion along with the building of the concept of gurukula, where teachers and sisya are live together in an educational institution. Moreover, when the West has not found an established educational system, India has built the world's earliest university Thaksashila or Taxila with a highly developed teaching system. But the progress of civilization in the past has not always been well inherited in the next era. Currently, Hindus especially in Indonesia are faced with Hindu-based education that is able to answer global challenges. Not only prosecuted to build superior human resources, but educational institutions are required to mastered technology as a global phenomenon. Hindu educational institutions were requested to be capable for becoming a modern gurukula as well as capable for realizing superior human resources.